Unveiling microRNA-like small RNAs implicated in the initial infection of Fusarium oxysporum f. sp. cubense through small RNA sequencing - Lifei Xie; Yuntian Bi; Chengcheng He; Junjian Situ; Meng Wang; Guanghui Kong; Pinggen Xi; Zide Jiang; Minhui Li (Mycology)
Banana Fusarium wilt (BFW), caused by Fusarium oxysporum f. sp. cubense (Foc), poses a major challenge to the worldwide banana industry. Fungal microRNA-like small RNAs (milRNAs) play crucial roles in regulating fungal growth, conidiation, development, and pathogenicity. However, the milRNAs and their functions in the pathogenesis of Foc remain poorly understood. In this study, we employed high-throughput sequencing and bioinformatics to profile Foc sRNAs during both pure culture and early infection stages. Our analysis identified six milRNAs exhibiting significantly upregulated expression at the initial Foc infection. Of these, milR106’s biogenesis was found to be Dicer-dependent, whereas milR87, milR133, milR138, and milR148 were associated with Dicer and Argonaute proteins. Genetic manipulation and phenotype analysis confirmed that milR106 is crucial for Foc virulence by regulating conidiation, hydrogen peroxide sensitivity, and infective growth. Gene Ontology analysis of milRNA targets in the banana genome revealed enrichment in defence response to fungus and cellular response to hypoxia, implying the importance of these target genes in response to pathogen infection. In conclusion, our sRNA profiling of Foc identified several infection-induced milRNAs. The corresponding results provide valuable molecular targets for the development of an efficient strategy to control BFW.